SISTEM INFORMASI GEOGRAFIS DALAM PENDATAAN PERTUMBUHAN PENDUDUK DIWILAYAH KECAMATAN KOTA TIMUR KOTA GORONTALO. - Djauhari, Mahbub; Serwin; Harun, Rofiq (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2025)
Abstract - Population growth data collection in Kota Timur Subdistrict has not been well organized. It impacts time inefficiency with limited data access by the community. This problem encourages the researcher to design a website-based Geographic Information System (GIS) application to facilitate the government's decision-making for appropriate development. This research aims to apply e-government technology in developing a GIS application to allow the urban villages and the community to access population growth data. The research result is a website application for a Geographic Information System in population growth data collection. It is designed as efficiently as possible so that it is easy for each neighborhood group head to input population growth data. It also makes it easy for the community to access population growth data in each urban village. Keywords : population growth data collection, GIS, decision making, e-government, data input efficiency